2004
DOI: 10.1002/ana.20126
|View full text |Cite
|
Sign up to set email alerts
|

Human T‐lymphotropic virus type II and neurological disease

Abstract: Human T-lymphotropic virus type I (HTLV-I) and type II (HTLV-II) are closely related retroviruses with similar biological properties and common modes of transmission. HTLV-I infection is endemic in well-defined geographic regions, and it is estimated that some 20 million individuals are infected worldwide. Although most infected individuals are asymptomatic carriers, some 2 to 5% will develop a chronic encephalomyelopathy, HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP). In contrast with HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 79 publications
(116 reference statements)
1
102
0
9
Order By: Relevance
“…HTLV-2 is prevalent in native populations, such as indigenous peoples in the Americas and Pygmy tribes in Africa, and in intravenous drug users [15][16][17][18][19] . Despite a 65% homology with HTLV-1, HTLV-2 has not been consistently associated with human disease; however, neurological disorders similar to HAM/TSP have been observed in patients with HTLV-2 infection 15,20 .…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-2 is prevalent in native populations, such as indigenous peoples in the Americas and Pygmy tribes in Africa, and in intravenous drug users [15][16][17][18][19] . Despite a 65% homology with HTLV-1, HTLV-2 has not been consistently associated with human disease; however, neurological disorders similar to HAM/TSP have been observed in patients with HTLV-2 infection 15,20 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies suggest that HTLV may be associated with a wider spectrum of neurologic manifestations that do not meet diagnostic criteria for HAM. These symptoms and conditions may later progress to HAM or constitute isolated neurologic syndromes associated with HTLV infection.…”
mentioning
confidence: 99%
“…It is not associated with any malignancies, but only with rare cases of subacute myelopathy like HAM/TSP, that have a more slowly progression (Araujo & Hall, 2004). However, HTLV-2 appears to be associated with an increased incidence of pneumonia, asthma and bronchitis, bladder and kidney infection, inflammatory conditions, such as arthritis, and with increased mortality, being suggested that HTLV-2 may inhibit immunologic responses to respiratory infections and induce inflammatory or autoimmune reactions (Roucoux & Murphy, 2004).…”
Section: Htlv-2: Biological Characteristics Pathogenesis and Epidemimentioning
confidence: 99%